The Effect Of Tofu Liquid Waste as Liquid Organic Fertilizer On The Growth and Production Of Cayenne Pepper (Capsicum Frutescens L. ) - Julianto, Helmy; Maretik, Maretik; Tendrita, Miswandi (Journal of Biological Science and Education, 2024)
This research aims to determine the effect of giving POC to tofu waste production of cayenne pepper plants, as well as knowing the effective POC dose for cayenne pepper plants. This research was carried out from November 2022 to January 2023 and took place in Sea Village, Kolaka Regency. This type of research includes experimental research consisting of 5 treatments and 4 replications to obtain 20 polybags with a total of 20 research plants. The parameters observed were the number of fruits (fruit) and fruit weight (grams). The research results show that from the parametric test using analysis of variance (ANOVA), the parameter data value for the number of fruit is 0.082 and the weight of the fruit is 0.225; the significance value is more than 0.05, thus H0 is accepted and H1 is rejected. So it can be concluded that there is no significant effect of giving tofu waste POC on the production of cayenne pepper plants. Keywords: Cayenne Pepper Plants ( Capsicum frutescens L.), Tofu Waste POC, and Production